OPTIMALISASI MANAJEMEN PERSEDIAAN DENGAN EOQ, ROP, DAN SAFETY STOCK - Ardianto, Ferri; Wardana, Ditya (RISTANSI: Riset Akuntansi, 2025)
Inventory management is a very important factor to be applied to retail companies. This is because merchandise inventory is a major component in operational activities. There are various inventory management methods that can be applied, including the Economic Order Quantity (EOQ), Reorder Point (ROP), and Safety Stock methods. This study aims to analyze the optimization of inventory management using the EOQ, ROP, and Safety Stock values at the company “ASK,” in order to determine the optimal and efficient amount of inventory to avoid stock outs and overstock. This research is a type of quantitative descriptive research. The population used in this study is the inventory of merchandise at the company “ASK.”, from this population a sample was taken in the form of 2x1.5mm 50m extrana nym cable. The data used is primary data which includes information about the inventory of 2x1.5mm 50m extrana nym cable during August - November 2024. The data that has been collected is then analyzed by applying the Economic Order Quantity (EOQ), Reorder Point (ROP), and Safety Stock methods. The results obtained are EOQ of 595.04 meters with an order frequency of 13 times in one period, a reorder point (ROP) of 770.8 meters, and a safety stock of 513.5 meters.